Establishment of a Necroptosis-Related Prognostic Signature to Reveal Immune Infiltration and Predict Drug Sensitivity in Hepatocellular Carcinoma - Ren, Huili; Zheng, Jianglin; Cheng, Qi; Yang, Xiaoyan; Fu, Qin (Frontiers in Genetics, 2022)
Background: Hepatocellular carcinoma (HCC) is the common type of primary liver cancer and had a poor prognosis. Recently, necroptosis has been reported to be involved in the progression of multiple cancers. However, the role of necroptosis in the HCC prognosis remains elusive. Methods: The RNA-seq data and clinical information of HCC patients were download from TCGA and ICGC datasets. Differential expressed genes (DEGs) and prognosis-related genes were explored, and non-negative matrix factorization (NMF) clustering algorithm was applied to divide HCC patients into different subtypes. Based on prognosis-related DEGs, univariate Cox and LASSO Cox regression analyses were implied to construct a necroptosis-related prognostic model. The relationship between prognostic model and immune cell infiltration, tumor mutational burden (TMB) and drugs response were explored. Results: 13 prognosis-related DEGs was confirmed from 18 DEGs and 24 prognostic-related genes. Based on the prognosis-related DEGs, patients in TCGA cohort were clustered into 3 subtypes by NMF algorithm, and patients in C3 had a better survival. A necroptosis-related prognostic model was established according to LASSO analysis, and HCC patients in TCGA and ICGC were divided into high- and low- risk groups. Kaplan-Meier (K-M) survival analysis revealed that patients in the high-risk group had a shorter survival time than the low-risk group. By univariate and multivariate Cox analyses, the prognostic model was identified as an independent prognostic factor and had better survival predictive ability of HCC patients compared with other clinical biomarkers. Furthermore, the results revealed that the high-risk patients had a higher stromal, immune, ESTMATE scores, TP53 mutation rate, TMB, and lower tumor purities than those in the low-risk group. In addition, there were significant differences in predicting drug response between the high- and low-risk groups. The protein and mRNA level of those prognostic genes was upregulated in HCC tissues compared normal liver tissues. Conclusion: We established a necroptosis-related prognostic signature that may guidance for individualized drug therapy in HCC patients and further experimentation is needed to validate these results.